Comprehensive review of single-crystal Ni-rich cathodes: single-crystal synthesis and performance enhancement strategies - Hong, Meihua; Ho, Van-Chuong; Mun, Junyoung (Frontiers in Batteries and Electrochemistry, 2024)
This review focuses on recent advancements in single-crystal Ni-rich cathodes for Li-ion batteries. An in-depth analysis is provided of the key characteristics of single-crystal Ni-rich cathodes and a description of the synthesis methods, performance degradation mechanisms, and enhancement strategies tailored to these materials is given. Synthesis techniques such as solid-state and molten salt syntheses are discussed in detail. Additionally, we describe some of the nuanced challenges and solutions pertaining to single-crystal Ni-rich cathodes, including surface modification (coating and additives) to improve the initial efficiency and Li diffusion rate through doping, with the aim of prolonging cyclability. This review offers comprehensive insights into the development of singlecrystal Ni-rich cathodes and suggests directions for advancing Li-ion battery technology using these specialized cathode materials.Recently, the demand for Li-ion batteries (LIBs) has grown exponentially with their applications in large-scale devices such as electric vehicles and energy storage systems (ESS). The energy density of LIBs directly affects the performance of these large devices, including the driving range of electric vehicles and operating time of ESS, making them critically important. Furthermore, frequent fluctuations in fuel prices and increasing air pollution have increased the importance of eco-friendly transportation methods, especially electric vehicles. To meet the rapidly expanding market demand, it is necessary to enhance the energy density of LIBs (Wakihara, 2001;Kebede et al., 2022;Natarajan and Aravindan, 2018).An LIB system composed of LiCoO2 and graphite was first developed by Sony in 1991(Ozawa, 1994). Initially, cathode LiCoO2 exhibits a layered crystalline structure that allows the lithiation and delithiation of Li ions along a two-dimensional plane. Cathode materials with such layered structure have high Li-ion conductivity during the charge and discharge processes because of strong ionic bonding in the metal oxide (M-O) layers formed, which interact with adjacent M-O layers through